2016
DOI: 10.1016/j.ejor.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain forecasting: Theory, practice, their gap and the future

Abstract: HIGHLIGHTSThe literature on supply chain forecasting is critically reviewed;The process of involving the forecasting community towards that task is described;Gaps between theory and practice are identified; Data and software related issues are explicitly considered; Challenges are summarised followed by suggestions for further research. ABSTRACTSupply Chain Forecasting (SCF) goes beyond the operational task of extrapolating demand requirements at one echelon. It involves complex issues such as supply chain coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
111
0
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 238 publications
(131 citation statements)
references
References 112 publications
0
111
0
20
Order By: Relevance
“…However, in the case of many homogeneous demand series and small samples, the top-down approach can generate more accurate forecasts (Jin, Williams, Tokar, and Waller, 2015;Zotteri and Kalchschmidt, 2007;Zotteri et al, 2005). For instance, different brands of ice cream will have a similar seasonality with a summer peak, which may not be easily detected for low-volume flavors but can be estimated at a group level and applied on the product level (Syntetos, Babai, Boylan, Kolassa, and Nikolopoulos, 2016). Song (2015) suggested that it is beneficial to model and forecast at the level of data where stronger and more seasonal information can be collected.…”
Section: Forecasting Within a Product Hierarchymentioning
confidence: 99%
“…However, in the case of many homogeneous demand series and small samples, the top-down approach can generate more accurate forecasts (Jin, Williams, Tokar, and Waller, 2015;Zotteri and Kalchschmidt, 2007;Zotteri et al, 2005). For instance, different brands of ice cream will have a similar seasonality with a summer peak, which may not be easily detected for low-volume flavors but can be estimated at a group level and applied on the product level (Syntetos, Babai, Boylan, Kolassa, and Nikolopoulos, 2016). Song (2015) suggested that it is beneficial to model and forecast at the level of data where stronger and more seasonal information can be collected.…”
Section: Forecasting Within a Product Hierarchymentioning
confidence: 99%
“…Therefore, the forecasting problem, from a practitioner perspective, reduces to finding meaningful minimum variance clusters from which forecasts can be constructed to support operational decision making. This problem is not unique to supply forecasting, as determining how to aggregate and forecast demand in multi-location and multi-product systems is an important area of research (See for example [51,52,53]).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Here, we are mainly concerned with the reverse loop and the forecasting of returns, as this is the additional aspect of supply uncertainty remanufacturers face; we refer the interest to Syntetos et al (2016) for a literature review on demand forecasting methods. Depending on the setting, these returns forecasts can be used on their own, or subtracted from the demand forecasts to obtain net demand forecasts.…”
Section: Forecasting In Closed-loop Supply Chainsmentioning
confidence: 99%